Multi-Criteria Decision Methods in the evaluation of social housing projects - Luque Castillo, Ximena; Yepes, Victor (Journal of Civil Engineering and Management, 2025)
The evaluation of social housing projects is a complex process that requires the consideration of multiple factors and dimensions to make informed decisions to address the emerging challenges of contemporary urbanization and achieve more resilient and sustainable communities. This study’s comprehensive review of the existing literature on the use of Multi-Criteria Decision Methods (MCDM) in evaluating social housing projects was undertaken. An exhaustive analysis of a bibliographic set of 93 articles published between 1994 and march 2025 was conducted. It was noted that the articles analyzed different phases of the construction process, from planning and design to implementation and maintenance. Significant trends in the use of MCDM were identified, highlighting the prevalence of crisp number-based approaches and the emergence of modern techniques such as fuzzy logic and neutrosophic logic. Among the most widely used methods were AHP and TOPSIS, both pioneering methods. In addition, there was an increasing focus on sustainability in project evaluation, encompassing environmental, social, economic, and technical aspects. Consequently, this literature review serves as a guide for incorporating multi-criteria evaluation strategies to improve constructability, especially in social housing projects, taking sustainability into consideration.